The Texas City Disaster, 1947 - Stephens, Hugh W. (University of Texas Press, 2021)
On April 16, 1947, a small fire broke out among bags of ammonium nitrate fertilizer in the hold of the ship Grandcamp as it lay docked at Texas City, Texas. Despite immediate attempts to extinguish the fire, it rapidly intensified until the Grandcamp exploded in a blast that caused massive loss of life and property. In the ensuing chaos, no one gave much thought to the ship in the next slip, the High Flyer. It exploded sixteen hours later. The story of the Texas City explosions-America's worst industrial disaster in terms of casualties-has never been fully told until now. In this book, Hugh W. Stephens draws on official reports, newspaper and magazine articles, personal letters, and interviews with several dozen survivors to provide the first full account of the disaster at Texas City. Stephens describes the two explosions and the heroic efforts of Southeast Texans to rescue survivors and cope with extensive property damage. At the same time, he explores why the disaster occurred, showing how a chain of indifference and negligence made a serious industrial accident almost inevitable, while a lack of emergency planning allowed it to escalate into a major catastrophe. This gripping, cautionary tale holds important lessons for a wide reading public